2021
DOI: 10.3390/nu13082577
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Markers in Adipose Tissue and Cardiovascular Risk Reduction by Pomegranate Juice in Obesity Induced by a Hypercaloric Diet in Wistar Rats

Abstract: Pomegranate juice (Punica granatum) has been used since ancient times in traditional medicine (Unani Medicine, Ayurveda); its main compounds are anthocyanins and ellagic acid, which have anti-inflammatory, antioxidant, hepatoprotective, and cardiovascular health effects. The objective was to evaluate the effect of pomegranate juice on inflammation, blood pressure, and vascular and physiological markers associated with obesity induced by a high-fat diet in a murine model. The results show that pomegranate juice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In the male reproductive system, it is believed that cytokines, whose origin are from Sertoli cells, Leydig cells, seminal vesicles, the epididymis, prostate, testicular macrophages, and male accessory glands, accumulate in the seminal plasma, which ultimately affects steroidogenesis, spermatogenesis, and sperm function [ 51 , 52 ]. Intercellular and vascular adhesion molecules, as well as chemokines, are responsible for the secretion of necrotic fat cells which cause the proliferation and movement of monocytes and macrophages to adipose tissues [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the male reproductive system, it is believed that cytokines, whose origin are from Sertoli cells, Leydig cells, seminal vesicles, the epididymis, prostate, testicular macrophages, and male accessory glands, accumulate in the seminal plasma, which ultimately affects steroidogenesis, spermatogenesis, and sperm function [ 51 , 52 ]. Intercellular and vascular adhesion molecules, as well as chemokines, are responsible for the secretion of necrotic fat cells which cause the proliferation and movement of monocytes and macrophages to adipose tissues [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…PJ is high in polyphenols and is renowned for its anti-AS and anti-inflammation characteristics ( Danesi and Ferguson, 2017 ). PJ results in a significant reduction of the atherosclerotic lesion size and intima media thickness, a 20% reduction in the absorption of ox-LDL and native LDL by peritoneal macrophages ( Aviram et al, 2000 ; Basu and Penugonda, 2009 ), a 27% rise in HDL content and a 12 to 18% reduction in the risk of CVD ( Michicotl-Meneses et al, 2021 ).…”
Section: Natural Products Regulate Gm and Inflammation In Asmentioning
confidence: 99%
“…Epidemiological studies observed that the consumption of fruits improved cardiac dysfunction. , It is worth noting that bioactive chemicals in fruits have potential to prevent or reverse cardiac dysfunction in diabetes . Ellagic acid (EA) is a natural polyphenol compound rich in many fruits and vegetables, especially pomegranate, strawberries, raspberries, and cranberries .…”
Section: Introductionmentioning
confidence: 99%